Antitrust for Internet Giants - Martin Taschdjian; James Alleman (International Telecommunications Society (ITS), 2018)
There can be no doubt that the FANG companies – Facebook, Amazon, Netflix and Google, as well as Twitter – have transformed society since their emergence. Like all social transformations, the changes wrought by their services have had ripple effects that are both positive and negative. On the positive side, soaring consumer access to information, news, social networks, and entertainment has been stimulated by the ever-more ubiquitous and falling prices of broadband fixed and mobile bandwidth. E-government has transformed the delivery of public services. However, negative effects have likewise been stark. Certainly, there have been huge disruptions caused by e-commerce. Retail industries, industrial supply chains, banking and publishing are just a few obvious examples. State tax collectors are fighting the loss of sales tax collections. These problems tend to get highlighted by the losers from the process of "creative destruction." Because Facebook and Google are two-sided markets, their economic rents are "hidden" from the public . On the user side of the market, prices are zero – "free." The other side, advertising rate are "hidden." Facebook's and Google's revenues are derived from advertising which appear when you go to their sites. They can extract exorbitant prices for ads, since they are virtually the only source that can target ads directly to potential clients. Because these companies can identify you, the ads can be targeted to your specific wants and needs, even creating "wants and needs" based on your profile. So, what the "customer" – you – perceived as free is not. Indeed, you are the commodity being sold to the advertisers. While Facebook and Google Herfindahl-Hirschman indices (HHI) are high, indicating a concentrated market or highly concentrated market by several different definitions of their markets. For example, Google has 93 percent of the search market. Combined Google and Facebook currently control over half of digital advertising and one-third of total advertising. Nevertheless, no serious antitrust case or legislation has addressed this monopoly power. This paper examines the antitrust cases against Facebook and Google. In this paper, we attempt to go back to first principles to discern whether there is a more appropriate approach to examine the underlying economics of these industries in the hopes that tools can be applied that more directly address the problems.
Keywords: D4; K2; L1; L2; L5; L9; 330; Advertising; antitrust; competition; internet; media; regulation; pricing